Faktor-Faktor yang Memengaruhi Partisipasi Sekolah Penduduk Usia 16-18 Tahun (SMASederajat) Di Provinsi Jawa Barat pada Tahun 2021 - Yosefina Yohana Nau Dewa; Achmad Prasetyo (Seminar Nasional Official Statistics, 2022)
Education is the basic capital in the development of a country. Thus, education is one of the development goals contained in the SDGs and the UUD 1945. During the COVID-19 pandemic, UNESCO estimates that out of 180 countries, around 24 million students will be at risk of dropping out of school. The school participation of the population aged 16-18 at the senior high school have a smaller percentage compared to the population elementary school and junior high schoo. In 2021, West Java Province has the lowest senior high school participation in Java and the third lowest in Indonesia, which is only 67.80 percent. This study uses the March 2021 Susenas data with the Binary Logistics Regression method. The results obtained in this study are the variables of gender, working status, KIP/PIP ownership status, cellular phone ownership status, head of household education, number of household members, area of ​​residence and household poverty status have a significant effect on school participation status.